Analisis Sistem Ketahanan Pangan di Provinsi Riau - Khaswarina, Shorea; Edwina, Susy; Kelari, Nur Islamiyanti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The growth of several food commodity production in Riau Province is decreasing and is not in line with the increasing need for food accompanied by increasing population growth. The imbalance between production and the level of food needs of each individual accompanied by increasing population growth each year can increase the opportunity for food vulnerability in an area. This research aims to analyze the status of food security from the aspect of food availability, the aspect of food affordability, and the aspect of food utilization in Riau Province. The method used in this research is the literature study method by collecting secondary data. The data used in this research is secondary data for the 2022 period which includes data from 10 districts and 2 cities in Riau Province. Data analysis was analyzed quantitatively descriptively. The results of this research show the condition of food security from the aspect of food availability with a ratio of normative consumption to cereal food availability of 4.98, meaning that food needs in Riau Province are four times the ability of Riau Province to produce food so that it is in a food deficit condition, where consumption needs food cannot be met from clean food production in Riau Province. Food security status from the aspect of food affordability is at moderate food security status. The food security status from the aspect of food utilization is at food security status, and the food security index for Riau Province is at food security status.